2015
DOI: 10.1080/15546128.2015.1009599
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of an Evidence-Based Teen Pregnancy Prevention Curriculum: A Case Study in a South Carolina School District

Abstract: Continued efforts are needed to reduce teenage pregnancy in the United States. Implementation of evidence-based curricula in schools is one strategy toward meeting this goal. In 2010, the South Carolina Campaign to Prevent Teen Pregnancy (SC Campaign) received funding to implement a teen pregnancy prevention (TPP) curriculum. Congruent with South Carolina law, the curriculum had to be approved by a school district advisory committee. A case study was conducted to explore factors that led to adoption of the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The fact that students in the comprehensive program still had slightly better outcomes suggests a further need to understand differences in school-level implementation and intervention components, given the importance of how these programs are selected and taught. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…The fact that students in the comprehensive program still had slightly better outcomes suggests a further need to understand differences in school-level implementation and intervention components, given the importance of how these programs are selected and taught. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the district leaders convened a committee of relevant stakeholders. In contrast to the findings reported by Workman et al (2015), committee members were not prepared for the task of evaluating science instructional materials and making an adoption recommendation, and the adoption criteria were flexible throughout the exploration stage.…”
Section: The Exploration Stage In Educationmentioning
confidence: 97%
“…Notably, fewer than one-third of the respondents indicated that they valued evidence of the effectiveness of the program when deciding to select and implement the program. Workman et al (2015) used case study methodology to document how one school district evaluated and selected sexuality education instructional materials. They found that the district leaders convened a committee of relevant stakeholders and evaluated the possible instructional materials using an evaluation tool designed for that purpose.…”
Section: The Exploration Stage In Educationmentioning
confidence: 99%
See 1 more Smart Citation